Effect of knowledge gain on species conservation status - Roberts, David (Lankesteriana: International Journal on Orchidology, 2015)
Following the 2002 World Summit in Johannesburg, the Convention of Biological Diversity (CBD) called for a decrease in the rate of biodiversity loss by 2010 (www.biodiv.org/2010-target).